Comparative Study on Different Types of Regression Applied to Unemployment in Maramures County of Romania - Tilca, Magnolia; Bojor, Meda (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2016)
We are studying the economic phenomenon of the unemployment in Maramures County of Romania. To obtain plausible conclusions regarding this study we apply different types of regression: the linear regression, polynomial regression, spline and Bspline regression. In this paper we focus on the numerical side of the research and we compare the predicted values, the graphic representation of the evolution, the future predictions and the errors generated by the regressions mentioned above. The calculations are performed in R, a programming language for statistical computing. An implementation in R is given.